A STUDY ON COLLISION OF TRAINING AND IMPROVEMENT FOR DELIVERY EXECUTIVES IN ZOMATO WITH REFERENCE TO CHENNAI - TAMILARASI, Dr. S . (The journal of contemporary issues in business and government, 2021)
Training is justify to be the assent the information of knowledge, along with the capability. Its particular intention to improve their employee knowledge, skills and their competency, participation and work rate of the employees. The main part the work of Human resource to operate Healthy training and growth, It’s previously mention that unique Training and Development is help to utilize the employees within limits of the firm. Hence the HR of firm will improve their outcomes and they improve the quality at corporate for this they need to be potential utilization. The present study evaluate the level of satisfaction among the delivery executives associate with their salaries, inducement along with the working surrounds and to identify the extent of the Zomato employees with management and working policies for Zomato delivery aggregators. Hypotheses devised to address the research questions were tested by SPSS.An overall sample of 120 delivery executives has been selected.